TRUSTED COMMONS: WHY “OLD” SOCIAL MEDIA MATTER - Maxigas, .; Latzko-Toth, Guillaume (AoIR Selected Papers of Internet Research, 2019)
Internet Studies scholarship tends to focus on new and hegemonic digital media, overlooking persistent uses of “older”, non-proprietary protocols and applications by some social groups who are key to configuring the nexus between technology and society. In response, we examine the contemporary political significance of using “old” social media through the empirical case of Internet Relay Chat (IRC) use. We advance a critique of platforms (closed, centralised, hegemonic social media) that we contrast with co-constructed devices that deeply involve users in their technological design and social construction. As a contemporary but long used online chat protocol, IRC serves as an important source for the critique of the currently hegemonic — but increasingly distrusted — infrastructures of computer-mediated communication. Drawing on Boltanski and Chiapello’s theory of critique and recuperation, we contrast the uses and underlying social norms of IRC with those of currently mainstream social media platforms. We claim that certain technical limitations that actors of IRC development did not feel necessary to address have kept it from incorporation into regimes of capital accumulation and social control, but also hindered its mass adoption. Ultimately, IRC continues to serve social groups key to the collaborative production of software, hardware and politics. While the general history of digital innovations illustrates the logic of critique and recuperation, our case study highlights the possibilities and pitfalls of resistance to it.